Soil Management Considerations to Improve Livestock Production - Pacheco-Hernández, Armando (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study conducted a meta-analysis to assess the importance of soil management in improving livestock production. Twenty-five empirical studies published between 2020 and 2025 that met specific inclusion and exclusion criteria were selected, focusing on soil management practices such as crop rotation, direct seeding, and cover crops. The search was conducted in academic databases such as Scopus, Web of Science, and Google Scholar, using relevant terms to ensure the quality and timeliness of the data. The results indicated that all soil management practices evaluated have significant positive effects on forage production and livestock health. Crop rotation showed a 15% increase in forage production, while direct seeding and cover crops increased production by 12% and 10%, respectively. The calculated effect sizes were 0.75, 0.68, and 0.62 for crop rotation, direct seeding, and cover crops, respectively, with moderate variability between studies. Subgroup analysis revealed that the practices were most effective in arid and semiarid regions and in dairy cattle systems. Although slight asymmetry in publication bias was identified, it was not found to significantly affect the results of the meta-analysis. Limitations of the study include variability in methodologies and quality of the studies. In conclusion, adopting sustainable soil management practices can significantly improve livestock production, highlighting the need to consider regional and livestock type-specific factors.